The Cambridge companion to American Catholicism - McGuinness, Margaret M.; Rzeznick, Thomas F. (Cambridge companions to religion, 2021)
"This Companion provides a comprehensive overview of American Catholicism's historical development and distinctive features. The essays - all specially commissioned for this volume - highlight the inner diversity of American Catholicism and trace the impact of American Catholics on all aspects of society, including education, social welfare, politics, and intellectual life. The volume also addresses topics of contemporary concern, such as gender and sexuality, arts and culture, social activism, and the experiences of Black, Latinx, Asian-American, and cultural Catholics. Taken together, the essays in this Companion provide context for understanding American Catholicism as it is currently experienced, and help to situate present-day developments and debates within their longer trajectory"--